The Requirements of the Sufi Path: A Defense of the Mystical Tradition - Ibn-Ḫaldūn, ʿAbd-ar-Raḥmān Ibn-Muḥammad (Library of Arabic Literature Series, 2022)
Intro -- Letter from the General Editor -- Abbreviations -- Acknowledgments -- Introduction -- Map: The Geography of Ibn Khaldūn's Lifetime -- Note on the Text -- Notes to the Introduction -- The Requirements of the Sufi Path -- Preface -- An Accurate Definition of the Sufi Path and How It Differs from the Paths Associated with the Divine Law -- What the Term "Sufi" Meant to Members of the Early Muslim Community -- Discussion of the Spiritual Struggles into Which the Sufis Were Led by Their Ardor, What Motivated These Struggles, and Why "Sufism" Had Originally Meant the First Spiritual Struggle but Came to Mean All of Them -- an Accurate Definition of this Path -- Discussion of the Spiritual Struggles, Their Divisions, and Their Prerequisites: Based on Our Study of Their Ideas and Perusal of Their Opinions, the Sufis Have Three Distinct Levels of Spiritual Struggle in a Fixed Hierarchy -- Discussing-and Refuting-How Modern Sufis Have Manipulated the Term "Sufism" -- When Is a Teacher Required, Recommended, or Unnecessary in the Spiritual Struggle? -- Presentation of the Two Sides of the Debate, of What Is Correct, and of My Verdict -- Notes -- Glossary of Names and Terms -- Bibliography -- Further Reading -- Index -- About the NYU Abu Dhabi Institute -- About this E-book -- Titles Published by the Library of Arabic Literature -- About the Editor-Translator.